Awareness-raising workshops on (geronto)technologies for elderly/family care: contributions to knowledge - Ilha,Silomar (2020)
ABSTRACT Objective: to describe the contributions of awareness-raising workshops to the knowledge of students in health courses about care (geronto)technologies for elderly people/family. Methods: a strategic action research, developed with 12 students from the last semester of nursing, physiotherapy, dentistry and occupational therapy from a university in Rio Grande do Sul, Brazil. Data were collected from September to December 2019, through semi-structured interviews, before and after awareness-raising workshops, and submitted to content analysis. Results: the analyzed data, before the workshops, allowed constructing two categories that dealt with lack of knowledge and non-use of care (geronto)technologies. After the workshops, five categories made it possible to understand (geronto)technologies in the form of products and in the form of processes/strategies/knowledge. Conclusion: carrying out awareness-raising workshops contributed to knowledge production regarding the conceptual aspect and identification of their usefulness in the care setting.